Dose-response eeffects oof aaqueous garlic eextract ssupplementation vvia ddrinking wwater oon ggrowth, hhematology, iimmunity, a and coccidiosis iin Japanese Quails (Coturnix Japonica) - Nhan, P.; Chuc, N. T.; Tri, N. M.; Mo, T. T. H.; Phuong, N. T. M. (Diponegoro University, 2025)
This research evaluated garlic extract addition to drinking water on growth performance, hemato-logical characteristics, survivability, and coccidial infection in Japanese quail (Coturnix japonica). There were 500 quails randomly allotted to four groups receiving 0, 1, 2, or 4 mL/L garlic extract for 35 days. Survival improved significantly in all garlic groups, especially 4 mL/L group, which kept 100% survivability within early duration and 99.2% upon termination of the experiment. Weight gain rose considerably with garlic addition, where 4 mL/L group achieved 196.08 ± 1.99 g at 35 days com-pared to 183.22 ± 1.02 g control group. Conversely, daily intake tended to be low in garlic groups, es-pecially in the finishing phase (27–35 days), in support of improved efficiency in feed intake. Hemato-logical findings indicated red blood cell and hemoglobin declined in a dose-related manner, yet white blood count significantly elevated, showing garlic's immunostimulation role. Additionally, shedding of oocyst considerably diminished in garlic-innoculated birds. At 35 days, 4 mL/L group showed 3.6 ± 0.2 log₁₀ oocysts/g feces.oocyst count, whereas 4.9 ± 0.3 log₁₀ were counted in 4 mL/L control, affirming a dose-related anti-coccidial action. These data indicate garlic extract from 2 to 4 mL/L can improve growth, immunity, and disease resistance of Japanese quail without any negative impact effects.